THE CURRENT SITUATION KNOWLEDGE OF DRUG PREVENTION AND CONTROL OF MALE MEDICINE STUDENTS IN THAI BINH UNIVERSITY OF MEDICINE AND PHARMACY IN 2020 (Vietnam Journal of Community Medicine, 2021)
The study was designed according to descriptive epidemiological research through an analytical cross-sectional investigation. Directly interviewing 434 male students of joint medicine at Thai Binh University of Medicine and Pharmacy in 2020. Research results: Describe knowledge of tobacco harm prevention and control of male students of Thai Binh University of Medicine and Pharmacy in 2020. Research shows that: The majority of study subjects (96.6% -98.9%) know that smoking cigarettes or passive smoking all affects their health. However, still 1.1% - 3.4% still do not know the harms of smoking. There are 88.9% of subjects who know about the law on tobacco harm prevention and control. Proportion of study subjects with correct knowledge of completely non-smoking places in the house and within the campus is from 79.3% -93.8%.
Keywords: Knowledge, male students, prevention, harm, tobacco